Enhancing strength and toughness of adhesive joints via micro-structured mechanical interlocking. (March 2021) - Hamilton, Alex; Xu, Yang; Kartal, Mehmet E.; Gadegaard, Nikolaj; Mulvihill, Daniel M.
Abstract: The potential to improve the mechanical properties of adhesive joints via micro-structured interlocking features is investigated. The micro-structured surfaces were fabricated in polycarbonate via injection moulding from a master template. The specimens were then bonded in an interlocking configuration to form single lap joints and tested to failure in tension. Planar untreated (i.e. un-abraded) and planar roughened (i.e. abraded) samples were also tested to provide benchmarks. Compared to the planar roughened case, results show that micro-structuring the interface can yield up to a 95.9% increase in strength and up to 162% increase in work to failure. Increases in strength and work to failure beyond the planar roughened level are attributed to mechanical interlocking of features. As deformation proceeds, progressive bending of each pair of interlocking features develops an increasing resistive load which allows the total load to significantly exceed that of the planar roughened case. Work to failure is increased via a combination of increased maximum force, increased displacement enabled by microfeature bending and a more torturous crack path. Low clearances between interlocking features were found to be favourable for mechanical properties owing to reduced bending stiffness of the repeating periodic unit at the interface.